Secondary Alveolar Bone Grafting and Iliac Cancellous Bone Harvesting for Patients With Alveolar Cleft. Issue 4 (June 2016) - Pan, Weiyi; Wu, Chenzhou; Yang, Zheng; Duan, Zexi; Su, Zhifei; Wang, Peiqi; Zheng, Qian; Li, Chunjie
Abstract : Abstract: To assess the efficacy of present interventions optimizing the result of secondary alveolar bone grafting (SABG) and the interventions alleviating the donor site morbidity after iliac cancellous bone harvesting. Researches were identified by searching the electronic database of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Chinese BioMedical Literature Database, and the China National Knowledge Infrastructure. In addition, relevant journals and references of the included studies were searched manually. The Oxford 2011 Levels of Evidence were applied to assess the methodological quality of selected studies, and the best evidence synthesis system was applied afterward to measure the strength of evidence. As a result, 42 studies were considered eligible and included, among which 4 were of high quality while 38 were of low quality. Thirty lines of evidences were acquired after the synthesis, among which 13 were rated as moderate while 17 were rated as insufficient. As for the interventions optimizing the result of SABG, moderate evidence confirmed the efficacy of preoperative orthodontic treatment, the superiority of performing SABG before the eruption of canine, and the accuracy of cone beam computed tomography in preoperative estimation of the cleft volume. As for the interventions alleviating the morbidity of iliac cancellous bone harvesting, moderate evidence confirmed the treatment benefit of the interventions below: minimally invasive technique, including trephine and Shepard osteotomy; preemptive analgesia, including continuous bupivacaine infusion or transversus abdominis plane block. As for the rest interventions, only insufficient evidence was found. Abstract : Supplemental Digital Content is available in the text